The status of civil society during the time of the Prophet (PBOH) (Salam International Academic Journal, 2019)
The prophet (PBOH) in his initial days of life in Madina (the holly City) was trying to figure out identify such a unique society  that respect and follow human and ethical values to guide the humanity toward righteousness, Allah and finding the truth. For this reason, he established Nabawi mosque to have a unified center of command that leads bilateral contract with Mahajerin and Ansar, dealing the Islamic unity contract amongst Muslims worldwide having a normal life with Jews and other religions could be considered some of the examples.This paper discusses the status of civil society during that time that is clearly stated in the amendment between Mahajerin and Ansars.If todays’ Muslims are capable of keeping the values of civil society implemented in Madina in their current life such as dedication, respect, values, helping each other, sympathy, ensuring social justice and many more, then it is undoubtedly possible that they retain and gain all the positive things that they have lost throughout these years and they will take back the stringy, independence, fulfilling the religious responsibility, most importantly, submitting their will to the one of the almighty Allah And as a result could find the path toward paradise.